2017
DOI: 10.1007/s40069-017-0190-y
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Cyclic Behavior of Precast Hybrid Beam-Column Connections with Welded Components

Abstract: Post-earthquake observations revealed that seismic performance of beam-column connections in precast concrete structures affect the overall response extensively. Seismic design of precast reinforced concrete structures requires improved beamcolumn connections to transfer reversed load effects between structural elements. In Turkey, hybrid beam-column connections with welded components have been applied extensively in precast concrete industry for decades. Beam bottom longitudinal rebars are welded to beam end … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 21 publications
(21 reference statements)
0
14
0
Order By: Relevance
“…In the draft version of TBEC [24], nonlinear analysis procedures were considered in deformation-based design of precast concrete structures. Performance limits for moment-resisting precast beam-column connections were determined according to ASCE/SEI 41 [5] considering experimental observations on MAB3 specimens tested by Girgin et al [6]. Performance limit states, and the corresponding drift ratios for precast connection tests are summarized in Table 2.…”
Section: Evaluation Of Beam-column Connectionsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the draft version of TBEC [24], nonlinear analysis procedures were considered in deformation-based design of precast concrete structures. Performance limits for moment-resisting precast beam-column connections were determined according to ASCE/SEI 41 [5] considering experimental observations on MAB3 specimens tested by Girgin et al [6]. Performance limit states, and the corresponding drift ratios for precast connection tests are summarized in Table 2.…”
Section: Evaluation Of Beam-column Connectionsmentioning
confidence: 99%
“…Damage pattern and lateral cyclic response of a precast beam-column connection is shown in Fig. Lateral load-drift ratio response for SP3-R specimen [6] Performance-based seismic evaluation of structures has gained attention for two decades to estimate the seismic risk in a realistic manner. Magliulo et al [7] performed nonlinear static and dynamic analyses on existing precast concrete structures considering all seismic components.…”
Section: Introductionmentioning
confidence: 99%
“…The results proved that the industrial type and residential type joint connections could be classified as low and medium ductility type connections, respectively. Similarly, Girgin et al [22] presented a similar beam-column connection using steel plates, which were welded to the lower beam reinforcement. The results showed that while increasing the embedded upper reinforcement of beam, the relative energy dissipation ratio was raised.…”
Section: Introductionmentioning
confidence: 99%
“…new connection for precast concrete frames (reprinted from[55], Copyright Elsevier, 2013) Girgin et al[56] investigated the seismic performance of hybrid beam-to-column connections that employed welded components. As can be seen fromFig.…”
mentioning
confidence: 99%
“…hybrid beam-to-column connection (reprinted from[56], Copyright Girgin, Sadik Can, Misir, Ibrahim Serkan, Kahraman, Serap, 2017)…”
mentioning
confidence: 99%